G504 Strategies employed to enhance recruitment and retenion in paediatrics: a scoping review. (25th October 2020) - Mallett, P; Thompson, A; Bourke, T
Abstract : Background: In the UK, the proportion of places available in medical school, the total number of foundation doctors, and the number of trainees applying to Paediatrics are falling. The NHS is at 'breaking point', exacerbated by workforce shortages, chronic underfunding, increasing service demand and poor job satisfaction within healthcare workers. Paediatrics in is in the midst of this crisis. Issues in recruitment and retention of paediatricians 'threaten the safety of our children's health' according to the Royal College of Paediatrics and Child Health. In 2019, the RCPCH Executive Committee has prioritised a new recruitment and retention campaign as their key strategic priority for the next three years. Aim: The aim of this study is to explore what strategies have been described in the literature that have been used to enhance recruitment and retention in Paediatrics. This is the first-known scoping review of the literature exploring specific strategies used globally to enhance recruitment and retention in Paediatrics. Methods: A scoping review methodology was conducted, employing a qualitative approach to review the literature on strategies used to improve recruitment and retention in Paediatrics. The studies included were English-language studies. 38 full-text articles were reviewed and analysed by the research team. Study Findings: Despite the importance of this issue, there is a paucity of data in the literature that describes evidence-based approaches to improving retention and recruitment in Paediatrics. The most important strategies employed to help are identified and collated using validated PRISMA criteria for systematic reviews. The findings were grouped into six main themes of professional advocacy, workforce diversity, mentorship, improving working conditions, career flexibility and enhancing educational opportunities. The authors propose a strategic modified 'Paediatric Pipeline' paradigm of 'Identify, Engage, Recruit, Retain and Champion.' Conclusions: There appear to be three main elements that are key to recruitment and retention of Paediatricians: personal, professional and systemic factors. Whilst some of the issues encountered share similarities with other medical specialities in difficulty, much of the context and potential remedies within Paediatrics are distinct. A strategic, multi-agency international collaborative approach is required urgently to address the significant issues that face both Paediatrics and the healthcare system itself.